MORAL REASONING INTERNAL AUDITOR DUKUNGAN MANAJEMEN SENIOR DAN MOTIVASI TERHADAP EFEKTIVITAS AUDIT INTERNAL DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI - Sari, Dewi Puspa; Afrida, Anggrelia (Balance : Jurnal Akuntansi dan Bisnis, 2021)
The problem of this research is an Effect of Moral Reasoning Internal Auditor, SeniorManagement Support, and Motivation of the Effectiveness of Internal Audit withOrganizational Culture as Moderating Variables (An Empirical Study of State-OwnedEnterprise Non Banking at Palembang South Sumatera). This type of research is associativeresearch. The data used are primary and secondary data. The population in this study is aninternal auditor in the State-Owned Enterprise total of 40 respondents. Data collectiontechniques by using interviews and questionnaires. Methods of data analysis used in thisresearch is the analysis of qualitative and quantitative analysis. Results showed that MoralReasoning of the auditors, Senior Management Support, and Motivationsignificantlypositively influence the effectiveness of Internal Audit. Organizational Culture moderate themoral reasoning internal auditor as a pure moderator of the Effectiveness of Internal Audit,Organizational Culture moderate the Senior Management Support as pure moderateof theEffectiveness of Internal Audit and Organizational Culture moderate Motivation of theEffectiveness of Internal Audit.